VIRAL MARKETING SEBAGAI ALTERNATIF STRATEGI PEMASARAN PRODUK SARIZ - Artika Surniandari (Widya Cipta - Jurnal Sekretari dan Manajemen, 2017)
Abstract - Creating a market that is widely known and benefited from the sale of goods offered by the promotional costs to a minimum is the expectation for all shopkeepers on line. By conducting observations and interviews in particular to the development of the sales of bags of knitting and creations knitted other products Sariz make its own interest for the author to introduce a form of marketing through the use of information technology that is social media as a means of promotion by creating a viral that will be distributed along with information about products offered.